Avaliação socioambiental da agricultura química e sua comparação com a agricultura natural - Iyama, Joaquim Tetsuo (2009)
The indiscriminate use of the natural resources, without observing its inter-relations with the global environment, has compromised the maintenance of the life Earth. The neoclassic economy believes that the environmental problem can be solved by on technology. On the other hand, the capitalist system stimulates the consumerism, and this is a way for the exhaustion of the natural resources and the environment pollution. The methods of the Chemical Agriculture, used by decades, has been very questioned because of the negative consequences the human health and the environment. It has been considered unsustainable by the main International Conferences on environment of the UNO (United Nations Organization). Hence, this work has the intention to make a comparative analysis between Chemical Agriculture and Natural Agriculture. by means of the situation thus, four land properties with same climatic conditions; altitude and geographic localization had been selected. Two of them located in the city of Cambuí - MG, with production of strawberry (a chemical one and a natural one), and the other two properties in Nova Friburgo RJ with cris lettuce production (on chemical and other natural). In order to have a comparative result between the two agricultural methods, in view of the ambient social-economic sustainability and on the health, one collected also, data through medical records on poisoning occurrences with agrotoxic chemicals (in the municipal district of Ribeirão Branco - SP, in 73 patients and in the municipal district of Nova Friburgo - RJ, in 44 patients) evidencing the problematic on of the agricultural production as a whole. As an evaluation tool, it will be used the method of Economic Valuation Method, that has been adopted as instrument to spread the knowledge, and to restrain actions leading to the annihilation of the environment, even so is not accepted for unanimity. At the same time, it has been an important tool to supply data and facilitate, for example, the indemnity of such environmental damage. Ahead of this great challenge. The proposal is to find a relieve and pragmatic way, that makes possible the economic development, without affecting too much the environment.